The Use of The Talaqqi Method to Improve Students' Understanding on Arabic Grammar in Class X Bilingual MA Nurul Islam Mojokerto - Almaliki, Muhammad Fikri; Afyuddin, Moh Sholeh (Proceeding International Conference on Education, 2024)
This research aims to analyze the use of the talaqqi method in improving students' understanding of the grammatical use of Arabic, especially fiil mudhori'. The talaqqi method, which is based on direct interaction between teachers and students, is expected to create a more dynamic and responsive learning environment. This research uses a qualitative approach with a case study design. Data was collected through participant observation, in-depth interviews with teachers and students, and analysis of learning documents. The research subjects included students and teachers of Arabic language class X Bilingual MA Nurul Islam Mojokerto who actively applied the talaqqi method in teaching grammar. The research results show that students feel more involved and motivated in learning Arabic when using the talaqqi method. Students reported increased understanding in the use of fiil mudhori', as well as the ability to better apply grammatical rules in writing. Direct interactions with teachers and classmates provide opportunities for students to ask questions, discuss, and receive constructive feedback. These findings emphasize the importance of the talaqqi method as an effective strategy in teaching Arabic, as well as implications for better teaching practices in the future. It is hoped that this research can be a reference for educators in designing more interactive and relevant learning approaches.